The Effects of Disease Models of Nuclear Actin Polymerization on the Nucleus - Serebryannyy, Leonid A.; Yuen, Michaela; Parilla, Megan; Cooper, Sandra T.; de Lanerolle, Primal (Frontiers in Physiology, 2016)
Actin plays a crucial role in regulating multiple processes within the nucleus, including transcription and chromatin organization. However, the polymerization state of nuclear actin remains controversial, and there is no evidence for persistent actin filaments in a normal interphase nucleus. Further, several disease pathologies are characterized by polymerization of nuclear actin into stable filaments or rods. These include filaments that stain with phalloidin, resulting from point mutations in skeletal α-actin, detected in the human skeletal disease intranuclear rod myopathy, and cofilin/actin rods that form in response to cellular stressors like heatshock. To further elucidate the effects of these pathological actin structures, we examined the nucleus in both cell culture models as well as isolated human tissues. We find these actin structures alter the distribution of both RNA polymerase II and chromatin. Our data suggest that nuclear actin filaments result in disruption of nuclear organization, which may contribute to the disease pathology.